Natural killer cell immunotypes related to COVID-19 disease severity - Maucourant, Christopher; Filipovic, Iva; Ponzetta, Andrea; Aleman, Soo; Cornillet, Martin; Hertwig, Laura; Strunz, Benedikt; Lentini, Antonio; Reinius, Björn; Brownlie, Demi; Cuapio, Angelica; Ask, Eivind Heggernes; et al. (Science immunology, 2020)
Understanding innate immune responses in COVID-19 is important to decipher mechanisms of host responses and interpret disease pathogenesis. Natural killer (NK) cells are innate effector lymphocytes that respond to acute viral infections but might also contribute to immunopathology. Using 28-color flow cytometry, we here reveal strong NK cell activation across distinct subsets in peripheral blood of COVID-19 patients. This pattern was mirrored in scRNA-seq signatures of NK cells in bronchoalveolar lavage from COVID-19 patients. Unsupervised high-dimensional analysis of peripheral blood NK cells furthermore identified distinct NK cell immunotypes that were linked to disease severity. Hallmarks of these immunotypes were high expression of perforin, NKG2C, and Ksp37, reflecting increased presence of adaptive NK cells in circulation of patients with severe disease. Finally, arming of CD56 NK cells was observed across COVID-19 disease states, driven by a defined protein-protein interaction network of inflammatory soluble factors. This study provides a detailed map of the NK cell activation landscape in COVID-19 disease.